Postoperative care after lymphaticovenous anastomosis - Chan, Jeffrey C.Y.; Taranto, Giuseppe Di; Elia, Rossella; Amorosi, Vittoria; Sitpahul, Ngamcherd; Chen, Hung-Chi (Archives of Plastic Surgery, 2021)
In this report, we discuss the postoperative protocol for patients undergoing lymphaticovenous anastomosis (LVA) in our unit. Immediately after LVA, the incision site is closed over a small Penrose drain and a simple gauze dressing is applied without compression. In the first 5 days, ambulation is allowed, but limb elevation is actively encouraged to promote lymphatic flow across the newly formed anastomosis. Prophylactic antibiotics are routinely given to prevent infection because this patient group is susceptible to infections, which could trigger thrombosis in the anastomosis.
Keywords: Lymphaticovenous anastomosis; Lymphedema; Postoperative care; Compression